2016
DOI: 10.1039/c6ob00131a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α,ω-polyfluorinated α-amino acid derivatives and δ,δ-difluoronorvaline

Abstract: Intending to synthesize ω,ω-difluoroalkyl amino acid derivatives by oxidative desulfurization-fluorination reactions of suitable arylthio-2-phthalimido butanoates and pentanoates, in addition to small amounts of the target products, mainly α,ω-polyfluorinated amino acid derivatives were formed by additional sulfur-assisted α-fluorination. This novel structural motif was verified spectroscopically as well as by X-ray analysis. A plausible mechanism of formation is suggested. Using a different approach, δ,δ-difl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…According to the literature, [12] N-bromosuccinimide (NBS) has frequently been used as a brominating agent for phenyl rings. [15] When pyridinium 4-toluenesulfonate (PPTS) was added, the isolated yield of dibromide 7 improved to 86 % (Table 1, entry 6). When the reaction mixture was heated at reflux for 8 h, only a trace amount of the target dibromide 7 was identified ( Table 1, entry 2).…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, [12] N-bromosuccinimide (NBS) has frequently been used as a brominating agent for phenyl rings. [15] When pyridinium 4-toluenesulfonate (PPTS) was added, the isolated yield of dibromide 7 improved to 86 % (Table 1, entry 6). When the reaction mixture was heated at reflux for 8 h, only a trace amount of the target dibromide 7 was identified ( Table 1, entry 2).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogenation of the benzyl group of 107 and oxidation of the resulting primary hydroxy group with DMP gave the corresponding aldehyde which was then treated with Deoxo-Fluor giving N -Phth-5,5-difluoronorvaline derivative 108 as the major product (Scheme ). During the fluorination reaction, the authors also observed an occurring cyclization reaction …”
Section: Fluorinated Alkyl α-Amino Acidsmentioning
confidence: 99%
“…During the fluorination reaction, the authors also observed an occurring cyclization reaction. 104 3.5.3. Methyl 2-((Boc)Amino-5,5,5-trifluoropentanoate (5,5,.…”
Section: T H Imentioning
confidence: 99%
“…Acyclic non-aromatic motifs are the most prevalent in naturally occurring amino acids. Therefore, the ability to access either fluorinated analogues or completely novel acyclic motifs is of utmost importance for applications such as biological probes and peptide therapeutics [ [133] , [134] , [135] , [136] , [137] , [138] , [139] ]. There have been many reports of the synthesis of singly fluorinated analogues of naturally occurring acyclic amino acids [ 12 ].…”
Section: Complex Fluorine-containing Non-aromatic Amino Acidsmentioning
confidence: 99%